2021
DOI: 10.1111/jen.12954
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short‐term heat stress on functional response ofNeoseiulus barkeritoTetranychus urticae

Abstract: The predatory mite Neoseiulus barkeri (Acari: Phytoseiidae) is typically used for biocontrol of Tetranychus urticae on strawberries. However, its biological characteristics are greatly affected by temperature in hot summer days. In this study, the influence of different short‐term heat stresses on the functional response and prey consumption of unmated female of N. barkeri on three stages (egg, protonymph and adult) of T. urticae was evaluated. Three temperatures (38, 40 and 42°C), three short‐term heat durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, few studies of thermal stress on the N. barkeri were found. Our previous work and another study all showed that the thermal stress negatively affected the longevity, reproduction characteristics ( Li et al, 2021 ), copulation ( Zhang et al, 2016 ), and functional response ( Li et al, 2022 ). Physiological mechanisms like the change of antioxidant enzymes of Neoseiulus barkeri, when faced thermal stress, were still not clear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, few studies of thermal stress on the N. barkeri were found. Our previous work and another study all showed that the thermal stress negatively affected the longevity, reproduction characteristics ( Li et al, 2021 ), copulation ( Zhang et al, 2016 ), and functional response ( Li et al, 2022 ). Physiological mechanisms like the change of antioxidant enzymes of Neoseiulus barkeri, when faced thermal stress, were still not clear.…”
Section: Discussionmentioning
confidence: 96%
“…We have found that the short-term heat stress does exert a negative effect on the longevity, reproduction characteristics, and functional response of N. barkeri. ( Li et al, 2021 ; Li et al, 2022 ). In this study, the physiological mechanism of N. barkeri in the response to the short-term heat stress based on relevant antioxidant enzymes was conducted, among which the eggs and the emerged adults were treated at 38, 40, and 42°C for 2, 4, and 6 h, then the changes in the enzyme activity were tested, which aims to clarify the effects of different short-term heat stresses and exposure durations on three protective enzymes in the body of N. barkeri .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of numerous attempts that have been made in recent years to study the impact of temperature on the developmental Antioxidants 2023, 12, 1998 2 of 14 rates of arthropods, there is little information related to mite pests at the molecular level [7]. High temperatures can cause a dramatic increase in ROS levels, leading to harmful effects on the population of N. barkeri [6,8,9] and resulting in suppressed potential and low control efficiency on small insects and mite pests [10].…”
Section: Introductionmentioning
confidence: 99%
“…Biological control is an environmentally friendly approach and an important component of most integrated pest management (IPM) programs (Seyahooei et al, 2018). Predatory mites, especially Phytoseiidae, are efficient natural enemies of phytophagous mites and have been used to control a range of pest mites and thrips (de Toledo et al, 2013; Ghazy & Amano, 2016; Kidane et al, 2015; Li et al, 2021; Shen et al, 2017). Neoseiulus bicaudus Wainstein (Acari: Phytoseiidae) is a predatory mite species recently observed in the Xinjiang Uygur Autonomous Region (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%